PENGARUH PROFITABILITAS, STRUKTUR, UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Umul Fadila (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2022)
This study aims to examine the effect of profitability, capital structure, firm size on firm value LQ-45 2019-2021. The background of this research problem is that the financial statements are a means of management in being responsible for the business activities carried out by the company based on capital resources. A good financial report is a financial report that contains complete information, where profit has the potential of information that is very important for internal and external parties of the company in making decisions. The literature review used in this study is Debt to equity is described to see the extent to which company assets are financed by debt compared to own capital, Return on equity (ROE) is a measurement of income (income) available to company owners (both shareholders and shareholders). common stock and preferred stock) for the capital they invest in the company, the size of the company is the size of the company seen from the amount of equity value, sales value or asset value and a company whose shares are the largest is very broad, every expansion of share capital will only have an effect that is small against the possibility of loss or displacement of control from the dominant party over the company. This study uses a quantitative method with a descriptive approach. Methods of data collection using financial statements. The sampling method used purposive sampling and the sample used was 22 companies. The data is analyzed using panel data analysis with Eviews 10. The results in this study show profitability, capital structure, firm size affect the firm value of LQ-45 2019-2021.